The integrated reporting movement meaning, momentum, motives, and materiality - Eccles, Robert G. (Hoboken John Wiley & Sons, 2015)
The Integrated Reporting Movement explores the meaning of the concept, explains the forces that provide momentum to the associated movement, and examines the motives of the actors involved. The book posits integrated reporting as a key mechanism by which companies can ensure their own long-term sustainability by contributing to a sustainable society. Although integrated reporting has seen substantial development due to the support of companies, investors, and the initiatives of a number of NGOs, widespread regulatory intervention has yet to materialize. Outside of South Africa, adoption remains voluntary, accomplished via social movement abetted, to varying degrees, by market forces. In considering integrated reporting?s current state of play, the authors provide guidance to ensure wider adoption of the practice and success of the movement, starting with how companies can improve their own reporting processes. But the support of investors, regulators, and NGOs is also important. All will benefit, as will society as a whole.
Includes bibliographical references and index.
Keywords: Corporation reports